"Sushi roll" technique for precise total tongue functional reconstruction using a pre-sutured femoral anterolateral myocutaneous flap. (November 2020) - Zhou, Xi; He, Zhi-Jing; Su, Yu-Xiong; Zhang, Sheng; Gong, Zhao Jian; Wu, Han Jiang
Highlights: The flexible design of the "sushi roll" technique enables the neotongue with a normal shape and protuberance. "Sushi roll" technique producing acceptable swallowing function and cosmesis. "Sushi roll" technique causes minimal damage to the donor site. Abstract: Objectives: Reconstruction of the total tongue after cancer resection remains one of the challenges in head and neck surgery. Inadequate reconstruction after subtotal or total glossectomy defects leads to poor quality of life. The aim of this study was to explore an economical, practical and effective flap design for functional tongue reconstruction. Material and methods: Sixty patients were randomly divided into two groups, namely, a "Sushi roll" technique group (30 patients) and a conventional surgery group (30 patients). Then, the patients underwent total or subtotal tongue reconstruction. Swallowing function, speech intelligibility, cosmetic results, and quality of life were assessed with the appropriate scales. Outcomes were analysed, and a p-value <0.05 was considered significant. Results: The perioperative recovery of the "Sushi roll" group was superior to that of the conventional group. Relative to patients in the conventional group, patients in the "Sushi roll" group showed significantly improved speech intelligibility (p = 0.025), cosmetic results (p < 0.001) and swallowing function (p < 0.001). Conclusion: The innovative "Sushi roll" anterolateral thigh myocutaneous flap approach for total tongue reconstruction creates a free neotongue tip with adequate volume and protuberance and causes minimal damage to the donor site, producing acceptable swallowing function and speech intelligibility.